1988
DOI: 10.1007/bf00257314
|View full text |Cite
|
Sign up to set email alerts
|

The hepatotoxicity of 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) in rats

Abstract: A few cases of liver involvement have been reported in patients receiving treatment with the antineoplastic nitrosourea CCNU. A single oral dose of 20 or 50 mg/kg CCNU in female Wistar rats induced an important increase in transaminases between day 2 and day 6, followed by a second, moderate increase between day 21 and day 28. Alkaline phosphatases and conjugated hyperbilirubinemia (threefold-increase) were noted for the two doses and were greater for the highest dose. Histological and ultrastructural studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The mean starting CCNU dose was 70.6 mg/m 2 (median, 71.4 mg/m 2 ; range, 54.9-81.3 mg/m 2 ) and the median number of CCNU doses administered was 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Seven (28%) dogs in group A and 9 (36%) dogs in group B received CCNU every 28 days alternating with vinblastine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean starting CCNU dose was 70.6 mg/m 2 (median, 71.4 mg/m 2 ; range, 54.9-81.3 mg/m 2 ) and the median number of CCNU doses administered was 3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Seven (28%) dogs in group A and 9 (36%) dogs in group B received CCNU every 28 days alternating with vinblastine.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,12 Rodents treated with very high doses of CCNU develop acute biliary stasis and hepatocyte necrosis leading to death. 13 The toxicity of CCNU was further investigated in healthy beagle dogs given a single dose of 4 mg/kg. 9 Histopathologic evaluation of liver biopsy samples showed Kupffer cell hyperplasia, cloudy swelling of hepatocytes, and periportal fibrosis in all treated dogs.…”
mentioning
confidence: 99%
“…Preclinical studies of CCNU have shown the drug to be a potent hepatotoxin in several species, including rats, dogs, and monkeys. 14,15,17,18,[20][21][22][23][24] When rats were given single high doses of CCNU PO, hepatic lesions occurred soon after treatment and consisted primarily of bile duct injury with associated cholestasis. Focal hepatocyte necrosis occurred later and was mainly periportal, suggesting hepatocyte injury was secondary to bile duct injury.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Ultrastructural changes included alterations of microtubules affecting all hepatocytes and bile canaliculi. 22 Preclinical studies in dogs receiving CCNU dosages ranging from 40 to 200 mg/m 2 (given all at once or divided over several days) revealed the dose-limiting adverse effect to be hematopoietic toxicity. Dogs treated with lower dosages survived hematopoietic toxicity but exhibited hepatic toxicity, renal toxicity, or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation